2017
DOI: 10.18632/oncotarget.15183
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal truncated hepatitis B virus X protein regulates tumorigenicity, self-renewal and drug resistance via STAT3/Nanog signaling pathway

Abstract: Hepatitis B virus (HBV) is a major risk factor of chronic liver disease and hepatocellular carcinoma (HCC). Random integration of HBV DNA into the host genome is frequent in HCC leading to truncation of the HBV DNA, particularly at the C-terminal end of the HBV X protein (HBx). C-terminally truncated HBx (HBx-ΔC) has been implicated in playing a pro-oncogenic role in hepatocarcinogenesis. However, the mechanism whereby HBx-ΔC1 contributes to hepatocarcinogenesis remains unclear. In this study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 30 publications
2
25
0
Order By: Relevance
“…34,35 One of the predominant HBV proteins in HCC is HBx, which activates oncogenes, leads to epigenetic modifications, modulates miRNAs and long non-coding RNAs and affects proliferation, apoptosis, metabolism, chemotherapy resistance and metastasis. [36][37][38][39][40][41] Here, we have identified HBxmediated inhibition of ZHX2 via miR-155 as another possible mechanism by which HBV influences HCC progression (Fig. 6c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34,35 One of the predominant HBV proteins in HCC is HBx, which activates oncogenes, leads to epigenetic modifications, modulates miRNAs and long non-coding RNAs and affects proliferation, apoptosis, metabolism, chemotherapy resistance and metastasis. [36][37][38][39][40][41] Here, we have identified HBxmediated inhibition of ZHX2 via miR-155 as another possible mechanism by which HBV influences HCC progression (Fig. 6c).…”
Section: Discussionmentioning
confidence: 99%
“…The miR-155 seed site in ZHX2 3 0 UTR was deleted for the 3 0 UTR-del mut. [36][37][38][39][40][41] Here, we have identified HBxmediated inhibition of ZHX2 via miR-155 as another possible mechanism by which HBV influences HCC progression (Fig. The pRL-TK plasmid was transfected into all cells as Renilla luciferase control.…”
Section: Discussionmentioning
confidence: 99%
“…The link between HBx-expressing and CSCs in HBV-related HCC has gradually become a research hotspots. It has been reported that HBx promoted a CD44 + CD133 + CSCs subset in malignant transformed L-02 cells and Huh7 cells, and HBx regulated tumorigenicity, self-renewal, and drug resistance in HCC cells [4,35,36]. In the present study, we selected two different HCC cells with distinct proportion of ABCG2 + subset, which Huh7 cells had a low ABCG2 + subset ratio and MHCC-97H had a high ABCG2+ subset ratio.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study had shown that HBx-ΔC promoted the appearance of a CD133 hepatic CSC subset and confer cancer and stem cell-like features in HCC [27] . It is associated with cancer cell invasiveness and reduction of apoptotic response, tumorigenicity, chemoresistance, and migration [27,28] .…”
Section: Hbvmentioning
confidence: 99%